Global trends and forecasts of cervical cancer and a real-world safety assessment of human papillomavirus vaccines in women: A systematic analysis of the Global Burden of Disease study 2021 and the Vaccine Adverse Event Reporting System database - Kai Yan; Guang Yang; Lixuan Yan; Li Wu; Yang Wang; Peifeng He; Qi Yu (PLoS ONE, 2026)
Background Cervical cancer (CCA) remains a major cause of morbidity and mortality among women globally, particularly in low- and middle-income countries. Although human papillomavirus (HPV) vaccination is central to prevention, safety concerns may affect vaccine acceptance. We integrated global disease-burden trends with real-world post-marketing safety data to provide complementary public health evidence for CCA prevention. Methods Using Global Burden of Disease (GBD) 2021 data, we assessed global prevalence, incidence, death, and disability-adjusted life years (DALYs) for women with CCA from 1990–2021, and applied age–period–cohort (APC) models to characterize temporal patterns. Bayesian APC models were used to project future incidence and death, with retrospective validation. For vaccine safety, adverse event (AE) reports following HPV vaccination in females (Cervarix, Gardasil, Gardasil 9; 2006–2025) were extracted from the Vaccine Adverse Event Reporting System (VAERS). We performed disproportionality analyses using four algorithms to identify reporting signals, with designated medical event (DME) screening and subgroup analyses by age and vaccine type. Results Globally, the age-standardized incidence rate of CCA decreased from 18.1 to 15.3 cases per 100,000 women from 1990 to 2021, while new cases increased from 0.41 million to 0.67 million. The highest incidence and death rates were observed in sub-Saharan Africa and selected Pacific Island countries. Projections suggest continued declines in age-standardized incidence and death through 2050, although the absolute burden will likely remain substantial. In VAERS, 41,731 HPV vaccine-related reports were identified; most were non-serious (80.9%). Syncope (ROR = 5.81, 95%CI:5.64–5.99), loss of consciousness (ROR = 5.26, 95%CI: 5.06–5.47) and pallor (ROR = 6.39, 95%CI: 6.10–6.70) were the most frequently reported events, and six potential DME-related signals were detected. Conclusions Despite declining age-standardized rates, CCA continues to impose a substantial global burden with marked regional disparities. Sustained HPV vaccine prevention efforts should be supported by epidemiological evidence and transparent, evidence-based safety communication.